The Occurrences of Heavy Metals in Water, Sediment and Wild Shrimps Caught from Barito Estuary, South Kalimantan, Indonesia - Herliwati, Herliwati; Rahman, Mijani; Hidayat, Achmad Syamsu; Amri, Ulil; Sumantri, Ika (HAYATI Journal of Biosciences, 2022)
The research investigated the occurrences of heavy metal (Pb, Cu, and Cd) in waters, sediments, and wild shrimps collected from the Barito River estuary. Water and sediment samples were collected from 11 study sites by purposive sampling. At the same time, shrimps samples were captured around the sites. The study showed low levels of heavy metals in water samples; those were: Cd